Ionospheric Cold Ions Detected by MMS Behind Dipolarization Fronts - Y. Xu; H. S. Fu; C. Norgren; S. Toledo‐Redondo; C. M. Liu; X. C. Dong (Geophysical Research Letters)
Abstract Traditionally, dipolarization front (DF) is a discontinuity at the leading edge of the high‐speed plasma jets, separating hot tenuous plasma from the denser ambient plasma. The particles behind the DF are usually hot population resulting from various heating and acceleration processes therein. Here, using Magnetospheric Multiscale (MMS) observations, we report that cold ions of ionospheric origin can be found behind the DFs. These cold ions move along the reconnected magnetic field lines directly from lobe during substorm, forming counter‐streaming cold ion flows behind the DFs. We find that cold ionospheric ions, as an additional population behind the DF, could increase ion density by ~50%. This indicates that the cold ions can change the gradients in the plasma density, such as the density‐driven instabilities near the DFs, and further affect the DF dynamics.